The impact of fatigue severity and depression level on the quality of life in individuals with Parkinson’s disease in Taiwan - Lin, Hung-Yu; Lin, Yi-Tung; Chiou, Chou-Ping; Pan, Hsueh-Hsing (Frontiers in Psychiatry, 2024)
Background: Patients diagnosed with Parkinson's disease undergo alterations in physical, psychological, and social functionality, with the psychological domain being particularly predisposed to inducing fatigue and depressive symptoms. Understanding the alterations occurring within a patient's body and mind and how these influence their overall quality of life is crucial.Purpose: This study sought to explore the predictive capacity of fatigue severity, the presence of depressive symptoms, and diverse demographic factors on the quality of life among individuals with Parkinson's disease.A cross-sectional correlational study was conducted at a teaching hospital in southern Taiwan. The research utilized a questionnaire survey to interview 133 study participants, focusing on the Quality of Life Scale, Depression Scale, Fatigue Severity Scale, Social Support Scale, and demographic attributes.Results: A total of 130 valid questionnaires were obtained. The results showed that Hoehn and Yahr stage, fatigue severity, and depression status could predict quality of life, explaining 51.1% of the total variance. These findings suggest that patients at advanced Hoehn and Yahr stages, experiencing more severe fatigue, and exhibiting higher levels of depression, tended to report a lower overall quality of life. Our findings suggest that, in addition to Hoehn and Yahr stage, the severity of fatigue and levels of depression significantly impact the quality of life in individuals with Parkinson's disease.Conclusions: Nurses need to understand the "stressful life events" and the changes in appearance and physical function that patients with Parkinson's disease face due to chronic degenerative diseases. Hence, apart from addressing patients' physiological needs, healthcare professionals should also offer appropriate care for psychological issues, such as depressive symptoms. Encouraging patients to participate in "counseling groups" can further bolster their social support networks, 3 enhancing their overall well-being and addressing comorbidities associated with chronic degenerative diseases.